Innovations in macroscopic evaluation of pancreatic specimens and radiologic correlation. (2016) - Triantopoulou, Charikleia; Papaparaskeva, Kleo; Agalianos, Christos; Dervenis, Christos
Highlights: The axial slicing technique offers many advantages in accurate estimation of tumors extend and staging. Cross-sectional axial imaging is the best technique for accurate radiologic-pathologic correlation. Correlation may explain any discrepancies between radiological and histopathological findings. Pathology correlation may offer a better understanding of the missed findings by imaging or pitfalls Abstract: The purpose of this study was to evaluate the feasibility of a novel dissection technique of surgical specimens in different cases of pancreatic tumors and provide a radiologic pathologic correlation. In our hospital, that is a referral center for pancreatic diseases, the macroscopic evaluation of the pancreatectomy specimens is performed by the pathologists using the axial slicing technique (instead of the traditional procedure with longitudinal opening of the main pancreatic and/or common bile duct and slicing along the plane defined by both ducts). The specimen is sliced in an axial plane that is perpendicular to the longitudinal axis of the descending duodenum. The procedure results in a large number of thin slices (3–4 mm). This plane is identical to that of CT or MRI and correlation between pathology and imaging is straightforward. We studied 70 cases of suspected different solid and cystic pancreatic tumors and we correlated the tumor size and location, the structure—consistency (areas of necrosis—hemorrhage—fibrosis—inflammation), the degree of vessels' infiltration, the size of pancreatic and common bile duct and the distance from resection margins. Missed findings by imaging or pitfalls were recorded and we tried to explain all discrepancies between radiology evaluation and the histopathological findings. Radiologic-pathologic correlation is extremely important, adding crucial information on imaging limitations and enabling quality assessment of surgical specimens. The deep knowledge of different pancreatic tumors' consistency and way of extension helps to improve radiologists' diagnostic accuracy and minimize the radiological-surgical mismatching, preventing patients from unnecessary surgery.